A bioassay to determine Poa annua responses to indaziflam - Pritchard, Benjamin D.; Vargas, Jose J.; Mahey, Mohit; Brosnan, James T.; Patterson, Eric L. (Frontiers in Agronomy, 2023)
Herbicide resistance within Poa annua is widespread in managed turfgrass systems. In 2020, a P. annua collection from a golf course in the southeastern United States was reported to be resistant to indaziflam as well as six other mode-of-action groups. This first report in 2020 suggests that turfgrass managers would benefit from a bioassay to screen other collections with putative indaziflam resistance. A dose-response experiment was conducted with ten concentrations of indaziflam (0, 250, 500, 667, 1000, 1143, 1333, 2000, 4500, and 9000 pM) in Gelrite® culture during 2021 and 2022. An herbicide-susceptible (S1) collection of P. annua, a resistant standard (Site 3A), and a collection with putative resistance to indaziflam (Site 18) were included in this experiment. Petri dishes were filled with 80 mL of Gelrite® (3.75 g L-1) containing technical grade (≥ 98%) indaziflam and rifampicin (1000 µg mL-1). Each plate was sealed with parafilm after placing 15 seeds of a single collection on the Gelrite® surface. At 14 days after seeding (DAS), the length of the radicle (mm) protruding from each seed was recorded with digital calipers. Indaziflam concentrations required to reduce root growth by 70% (EC70) were calculated via non-linear regression. Statistically significant differences were detected among P. annua collections with the EC70 values for the herbicide-susceptible collection measuring 708 pM [95% confidence interval (CI) = 656 to 764 pM] compared to 2130 pM (CI = 1770 to 2644 pM) for Site 3A and 4280 pM (CI = 3464 to 5442) for Site 18. Given that resistant collections exhibited longer root length in the absence of herbicide, confocal microscopy analysis was used to explore differences in root cell count among resistant and susceptible P. annua collections; however, few differences in cell count were detected. Overall, these findings indicate that a discriminatory dose of 708 pM (95% CI = 656 to 764 pM) can be used to differentiate among susceptible and resistant P. annua collections from field sites where poor control is observed following broadcast applications of indaziflam.